The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1007/pl00007792
|View full text |Cite
|
Sign up to set email alerts
|

Treatment and outcome of severe intraventricular extension in patients with subarachnoid or intracerebral hemorrhage: a systematic review of the literature

Abstract: Severe intraventricular hemorrhage caused by extension from subarachnoid hemorrhage or intracerebral hemorrhage leads to hydrocephalus and often to poor outcome. We conducted a systematic review to compare conservative treatment, extraventricular drainage, and extraventricular drainage combined with fibrinolysis. We carried out a search in Medline of the literature between January 1966 and December 1998 and an additional hand-search from January 1990 to December 1998. Pharmaceutical companies were contacted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
2
12

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(129 citation statements)
references
References 21 publications
7
108
2
12
Order By: Relevance
“…The statistic data have shown that the case fatality rate for conservative treatment of severe IVH was 78%, and it was 58% for EVD performed by conventional drilling technique. 1 In our study, the mortality rate of 3773 cases with rapid pore drilling was only 24.8%, and the mortality rate for patients with severe conditions such as aneurysm rupture and cerebral arteriovenous hemorrhage was slightly higher (.30%), yet still significantly lower than the historical comparator. However, this comparison was made from indirect observational studies using historic data.…”
Section: Discussioncontrasting
confidence: 48%
“…The statistic data have shown that the case fatality rate for conservative treatment of severe IVH was 78%, and it was 58% for EVD performed by conventional drilling technique. 1 In our study, the mortality rate of 3773 cases with rapid pore drilling was only 24.8%, and the mortality rate for patients with severe conditions such as aneurysm rupture and cerebral arteriovenous hemorrhage was slightly higher (.30%), yet still significantly lower than the historical comparator. However, this comparison was made from indirect observational studies using historic data.…”
Section: Discussioncontrasting
confidence: 48%
“…22 Although IVH per se may be detrimental for neurological recovery, there is no definite proof that EVD has a beneficial effect in patients without symptomatic hydrocephalus. 18 Our results indicate that it is reasonable to observe patients with IVH (even those with panventricular involvement) as long as they do not have symptomatic hydrocephalus. Yet, these patients must be monitored closely, especially if they have very extensive IVH, coma without hydrocephalus, or dilation of the fourth ventricle.…”
Section: Discussionmentioning
confidence: 52%
“…Помимо системного фибринолиза при ишемическом инсульте и локального фибринолиза при геморрагическом ин-сульте с 90-х гг. стало развиваться принципиально новое направление использования фибринолитиков -интрате-кальный фибринолиз при субарахноидальных и внутри-желудочковых кровоизлияниях (ВЖК) нетравматическо-го генеза [10][11][12][13][14][15].…”
Section: история вопросаunclassified